HIV-associated Neuropathy and Autonomic Dysfunction in South Africans on established ART impacts daily living - Dudley, Meagan Taryn (Department of Medicine, 2021)
Introduction A common complication of Human Immunodeficiency Virus (HIV) and anti-retroviral therapy (ART) is distal sensory polyneuropathy (DSP). Older age and previous TB are risk factors for DSP among HIVinfected Africans before and shortly after ART initiation. Little is known about autonomic dysfunction in Africans on long-term ART and the impact of DSP and autonomic impairment on their quality of life. Our aim was to describe the frequency, characteristics and functional consequences of DSP and autonomic dysfunction in a healthy HIV-infected community-based cohort after at least 5 years of ART. Methods HIV-infected South Africans on the government-sponsored ART program for at least 5 years were included in this cross-sectional analysis. Each consenting participant underwent a focussed neurological assessment using the Brief Peripheral Neuropathy Screen (BPNS) and a reduced version of the Total Neuropathy Score (rTNS). DSP was defined as the presence of at least 2 neuropathic signs in a distal and symmetrical distribution, and symptomatic DSP (SDSP) when accompanied by neuropathic symptoms. Heart rate variability and orthostatic hypotension were measured as described by the Ewing classic battery, and the Survey of Autonomic Symptoms (SAS) questionnaire assessed the presence and severity of autonomic symptoms. We used a modified version of the Lower Extremity Functional Scale (LEFS) to assess lower limb physical ability. Results The 67 participants had a median age of 41 years (interquartile range (IQR) 36-46) and 61 (91 %) were women. The median duration of ART was 7 years (IQR 6-10). DSP criteria were met in 54 (80.6%) and 24 (44.4%) had symptomatic DSP. Comparing participants with DSP to those without DSP, there was no difference in sex (P=0.39), age (P=0.79), current CD4 (P=0.69), viral suppression (P=0.34), ART duration (P=0.22) or previous tuberculosis (TB) (P=0.72) in those with DSP. Similar outcomes were obtained for SDSP. Abnormal autonomic tests were present in 60%. Those with SDSP had more severe autonomic symptoms than those with asymptomatic DSP (P=0.0008). We found that those with DSP and SDSP had significantly lower LEFS percentage scores than those without (P=0.039 and P=0.013 respectively). 5 Conclusion DSP remains a common complication of HIV in the modern era of ART and can lead to significant functional impairment. Autonomic dysfunction is prevalent in SDSP.